Coordinated scheduling via frequency and power allocation optimization in LTE cellular networks - Trabelsi, Nessrine; Chen, Chung Shue; Roullet, Laurent; Altman, Eitan; El Azouzi, Rachid (IEEE/IFIP Network Operations and Management Symposium, 2016)
Due to Orthogonal Frequency Division Multiple Access (OFDMA) mechanism adopted in LTE cellular networks, intra-cell interference is nearly absent. Yet, as these networks are designed for a frequency reuse factor of 1 to maximize the utilization of the licensed bandwidth, inter-cell interference coordination remains an important challenge. In both homogeneous and heterogeneous cellular networks, there is a need for scheduling coordination techniques to efficiently distribute the resources and mitigate inter-cell interference. In this paper, we propose a dynamic solution of inter-cell interference coordination performing an optimization of frequency sub-band reuse and transmission power in order to maximize the overall network utility. The proposed framework, based on game theory, permits to dynamically define frequency and transmission power patterns for each cell in the coordinated cluster. Simulation results show significant benefits in average throughput and also cell edge user throughput of 40% and 55% gains when performing the frequency sub-band muting and power control. Furthermore, we also obtain a meaningful improvement in energy efficiency.